PENYUSUNAN LAPORAN KEUANGAN BERBASIS MICROSOFT EXCEL BERDASARKAN SAK EMKM PADA CV MUSI COPIRINDO - Dwi Putri, Silvani; Martini, Rita; Armaini, Rosy (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2024)
Abstract The writing of this Final Report aims to determine the preparation of financial statements by CV Musi Copirindo based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The data used in the preparation of this final report was obtained from the company through interviews, documentation and literature study. The data used in analyzing the problem is cash expenditure and receipt data, asset data and company equity. The results of the analysis show that CV Musi Copirindo has not recorded transactions in an integrated manner into general / special journals and ledgers and has not presented financial reports based on SAK EMKM. The author suggests that CV Musi Copirindo record all of its business financial transactions in an integrated manner based on Microsoft excel so that it can prepare financial reports in subsequent periods easily and be able to apply the preparation of financial statements based on SAK EMKM.